Biological magnesium alloy micro-arc oxidation coating supercritical hole sealing method based on thermodynamic sedimentary phase diagram
By adopting a supercritical pore sealing method based on thermodynamic deposition phase pattern on the microarc oxidation coating of magnesium alloy, supercritical carbon dioxide permeates and seals pores through the deposition reaction of metal ions, the problem of poor sealing effect of magnesium alloy microarc oxidation coating in the prior art is solved, and the corrosion resistance of magnesium alloy is significantly improved.
Patent Information
- Application Number
- CN202411134678.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-04-25
AI Technical Summary
The existing microarc oxidation coating of magnesium alloy has poor effect, resulting in corrosive media penetration and affecting the corrosion resistance of the coating.
Using a supercritical pore sealing method based on thermodynamic deposition phase diagram, phosphate is used as the sealing solution component, and the carbon dioxide generated by NaH2PO4 and NaHCO3 reaction in a supercritical carbon dioxide environment is cooled into supercritical carbon dioxide, fully penetrates into the micropores of the microarc oxidation coating, and the pores are closed by the deposition reaction of metal ions.
A good sealing effect is achieved, the corrosion resistance of magnesium alloy is greatly improved, and the rate of sealing reaction can be quickly improved, and the H2 absorption capacity is good.
Smart Images

Figure CN119877059A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of magnesium alloy surface treatment technology, and in particular to a supercritical sealing method for a bio-magnesium alloy micro-arc oxidation coating based on a thermodynamic deposition phase diagram. Background Technology
[0002] Magnesium and magnesium alloys are the third largest metallic engineering material after iron-based and aluminum-based materials, with wide applications in many fields such as aerospace, automotive, 3C electronics, and biomedicine. Furthermore, magnesium is recyclable and reusable, making it a virtually inexhaustible metal, and it is hailed as a "green metallic structural material of the 21st century." However, the corrosion problem of magnesium and magnesium alloys has not been effectively solved, and their corrosion resistance has become a bottleneck restricting their further development.
[0003] From the perspective of corrosion science, the root cause of magnesium alloy corrosion lies in the inability of magnesium alloy surfaces to spontaneously form a protective surface film. Therefore, developing protective surface treatment technologies for magnesium alloys is of paramount importance.
[0004] Micro-arc oxidation (MAO), also known as plasma electrolytic oxidation (PEO), is a relatively new technique for in-situ growth of porous ceramic coatings on the surfaces of metals such as aluminum, titanium, and magnesium alloys. Its working principle involves using magnesium and its alloys as the anode and stainless steel or similar materials as the cathode in an alkaline electrolyte. Under high voltage or high current density conditions, when the voltage reaches the critical voltage (breakdown voltage), a micro-arc discharge occurs on the metal surface, forming a discharge channel. This ultimately results in the in-situ growth of a porous ceramic coating with high bonding strength and uniformity on the magnesium and its alloy surfaces. Compared to traditional anodizing techniques, MAO uses higher voltages (>200V) and current densities, and has a shorter processing time. Furthermore, the high voltage generates a large amount of heat, allowing the local temperature of the sample surface to reach over 1000°C. The resulting MAO coating is more uniform and denser, thicker, harder, and exhibits better corrosion and wear resistance than anodized coatings.
[0005] However, the surface of micro-arc oxidation coatings contains micropores of varying sizes. This allows corrosive media to penetrate the microporous layer and corrode the internal dense layer or even the substrate, severely affecting the coating's corrosion resistance and resulting in insignificant protection for the substrate. Therefore, after applying the micro-arc oxidation coating as the base layer, a sealing treatment is necessary to seal the micropores and microcracks on the coating surface. This reduces the porosity of the coating surface, making it denser and preventing corrosive media from penetrating and eroding the coating or even the substrate. This further improves the corrosion resistance of the micro-arc oxidation coating and achieves more effective protection for the substrate.
[0006] In recent years, researchers have attempted to use methods such as liquid phase deposition, electrochemical deposition, sol-gel method, and polymer coating to prepare alternative ceramic or organic polymer coatings to cover or seal the pores on the surface of micro-arc oxidation coatings, thereby altering the coating's properties. Generally, after pore sealing treatment, the corrosion resistance, bioactivity, and compatibility of micro-arc oxidation coatings are often significantly improved.
[0007] However, current sealing methods typically involve immersing magnesium alloys with a micro-arc oxidation coating on their surface in a sealing solution. An electrochemical / chemical reaction within the pores generates a conversion film, which then fills the pores of the magnesium alloy's micro-arc oxidation coating. These sealing methods are performed from the outside in, making it difficult for the gas generated during the sealing process to escape. This significantly hinders pore filling and results in limited sealing effectiveness.
[0008] Therefore, there is an urgent need for a better sealing method for magnesium alloy micro-arc oxidation coatings. Summary of the Invention
[0009] The technical problem to be solved by this invention is to provide a supercritical sealing method for bio-magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram with better sealing effect.
[0010] To address the aforementioned technical problems, this invention provides a supercritical sealing method for micro-arc oxidation coatings on bio-magnesium alloys based on thermodynamic deposition phase diagrams, comprising the following steps:
[0011] Using phosphate as the sealing solution component, phosphate ionization equilibration at different pH values was established, and the distribution pattern of phosphate ions in the phosphate system as a function of pH was obtained.
[0012] Deposition-dissolution equilibrations of metal ion phosphides and hydroxides in phosphate conversion membranes under different pH values were established in a supercritical carbon dioxide environment, and thermodynamic deposition phase diagrams were obtained.
[0013] Based on the thermodynamic deposition phase diagram, NaH2PO4 solution was selected and NaHCO3 was added to obtain the sealing solution;
[0014] The sealing solution is injected into the reactor and heated, and then the chiller is turned on to convert the generated carbon dioxide gas into supercritical carbon dioxide.
[0015] The micro-arc oxidized bio-magnesium alloy was placed in a sealing solution in a reaction vessel and pressurized to seal the micro-arc oxidized coating on the surface of the bio-magnesium alloy.
[0016] Furthermore, when the pH of the NaH2PO4 solution is controlled at 4-6, NaHCO3 is added to raise the pH of the solution to 5.5-6.6 to obtain a sealing solution.
[0017] Furthermore, NaHCO3 is added to the NaH2PO4 solution to raise the pH of the sealing solution to 6.
[0018] Furthermore, the sealing solution is injected into the reactor and then heated to a temperature of 40°C to 80°C.
[0019] Furthermore, the sealing solution is injected into the reactor and then heated to a temperature of 60°C.
[0020] Furthermore, the pressure of the bio-magnesium alloy after micro-arc oxidation in the sealing solution inside the reactor is 8 MPa to 15 MPa.
[0021] Furthermore, the pressure of the bio-magnesium alloy after micro-arc oxidation in the sealing solution inside the reactor is 10 MPa.
[0022] Furthermore, the micro-arc oxidation coating on the surface of the bio-magnesium alloy is sealed in the sealing solution in the reactor for 10 min to 20 min.
[0023] Furthermore, the micro-arc oxidation coating on the surface of the bio-magnesium alloy is sealed in the sealing solution in the reactor for 15 minutes.
[0024] Furthermore, the micro-arc oxidation of the bio-magnesium alloy includes the following steps:
[0025] The Mg-Zn-Ca bio-magnesium alloy was wire-cut into semi-cylindrical samples with a diameter of 10 mm and a height of 15 mm.
[0026] Drill a 3mm diameter hole on the side of the sample, and use a tap to machine an internal thread in the hole for subsequent wire connection;
[0027] The sample surface was polished in sequence with silicon carbide sandpaper of grades 240#, 600#, 1000# and 2000#, and then cleaned and dried to obtain a bio-magnesium alloy sample.
[0028] The cathode of the micro-arc oxidation power supply is connected to a graphite plate, and the anode is connected to the bio-magnesium alloy sample by an aluminum alloy wire.
[0029] Prepare the electrolyte: 20.0 g / L Na2SiO3·9H2O, 2.0 g / L NaOH and 3.3 g / L KF·2H2O, pH=13;
[0030] Power is turned on, and the semi-cylindrical sample of bio-magnesium alloy in the electrolyte is subjected to micro-arc oxidation until a micro-arc oxidation coating is formed on the surface of the bio-magnesium alloy.
[0031] Magnesium alloy micro-arc oxidation coatings were prepared using a pulsed mode, with the following electrical parameters: voltage 380±10V, current density 3A / dm³. 2The duty cycle is 30%, and the processing time is 30±2 min.
[0032] This invention provides a supercritical sealing method for micro-arc oxidation coatings of bio-magnesium alloys based on thermodynamic deposition phase diagrams. Using these phase diagrams as a foundation, a solution formed by adding NaH2PO4 and NaHCO3 is selected as the sealing solution. Through heating and cooling, the carbon dioxide gas generated in the reaction is converted into supercritical carbon dioxide. This supercritical carbon dioxide is introduced into the sealing system to seal the micro-arc oxidation coating of the bio-magnesium alloy. This method fully utilizes the superior properties of supercritical CO2 fluid, such as high diffusion capacity (like a gas), low surface tension, and high density (like a liquid). The entropy of the sealing solution system is increased by nearly 60 times compared to atmospheric pressure, allowing the sealing solution to fully penetrate the micropores of the micro-arc oxidation coating. The pores are sealed through the deposition reaction of metal ions, achieving excellent sealing results and significantly improving the corrosion resistance of the metal. It also greatly increases the rate of the sealing reaction and exhibits good H2 absorption capacity, thus solving the problem of poor sealing effect caused by gas difficulty in escaping and hindering pore filling in traditional sealing processes. Attached Figure Description
[0033] Figure 1 A flowchart of a supercritical sealing method for a micro-arc oxidation coating of bio-magnesium alloy based on a thermodynamic deposition phase diagram is provided for an embodiment of the present invention.
[0034] Figure 2 The graph shows the variation of the distribution coefficient δ of phosphoric acid ionization obtained in the supercritical sealing method for micro-arc oxidation coating of bio-magnesium alloy based on thermodynamic deposition phase diagram provided in the embodiments of the present invention.
[0035] Figure 3 The deposition diagram of the phosphate system at 0.1 mol / L obtained in the supercritical sealing method for micro-arc oxidation coating of bio-magnesium alloy based on thermodynamic deposition phase diagram provided in the embodiments of the present invention;
[0036] Figure 4 The images show the surface and cross-sectional SEM images of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 1 of the present invention.
[0037] Figure 5 A cross-sectional elemental distribution diagram of the coating of the bio-magnesium alloy after pore sealing obtained by the pore sealing method provided in Embodiment 1 of the present invention;
[0038] Figure 6 XRD analysis image of the bio-magnesium alloy coating after sealing pores obtained by the sealing method provided in Embodiment 1 of the present invention;
[0039] Figure 7EIS spectrum of the coating of bio-magnesium alloy after sealing by the sealing method provided in Embodiment 1 of the present invention during long-term immersion;
[0040] Figure 8 Macroscopic morphology of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 1 of the present invention after immersion in SBF solution;
[0041] Figure 9 The images show the surface and cross-sectional SEM images of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 2 of the present invention.
[0042] Figure 10 EIS spectrum of the coating of bio-magnesium alloy after sealing by the sealing method provided in Embodiment 2 of the present invention during long-term immersion;
[0043] Figure 11 Macroscopic morphology of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 2 of the present invention after immersion in SBF solution;
[0044] Figure 12 The images show the surface and cross-sectional SEM images of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 3 of the present invention.
[0045] Figure 13 EIS spectrum of the coating of bio-magnesium alloy after sealing by the sealing method provided in Embodiment 3 of the present invention during long-term immersion;
[0046] Figure 14 Macroscopic morphology of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 3 of the present invention after immersion in SBF solution;
[0047] Figure 15 The images show the surface and cross-sectional SEM images of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 4 of the present invention.
[0048] Figure 16 XRD analysis image of the bio-magnesium alloy coating after sealing pores obtained by the sealing method provided in Embodiment 4 of the present invention;
[0049] Figure 17 EIS spectrum of the coating of bio-magnesium alloy after sealing by the sealing method provided in Example 4 of this invention during long-term immersion;
[0050] Figure 18 Macroscopic morphology of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 4 of the present invention after immersion in SBF solution;
[0051] Figure 19The above images show the surface and cross-sectional SEM images of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 5 of the present invention.
[0052] Figure 20 EIS spectrum of the coating of bio-magnesium alloy after sealing by the sealing method provided in Embodiment 5 of the present invention during long-term immersion;
[0053] Figure 21 The image shows the macroscopic morphology of the bio-magnesium alloy coating obtained by the sealing method provided in Embodiment 5 of the present invention after immersion in SBF solution. Detailed Implementation
[0054] See Figure 1 The present invention provides a supercritical sealing method for a micro-arc oxidation coating of bio-magnesium alloy based on a thermodynamic deposition phase diagram, comprising the following steps:
[0055] Step 1) Using phosphate as the sealing solution, establish phosphate ionization equilibria at different pH values, and plot the phosphate distribution pattern of the phosphate system as a function of pH. The resulting phosphate distribution pattern of the phosphate system as a function of pH is shown in the figure below. Figure 2 As shown.
[0056] Step 2) Based on the phosphate distribution diagram of the phosphate system with pH variation, establish the deposition-dissolution equilibrium of phosphate conversion membranes in a supercritical carbon dioxide environment for the corresponding phosphides and hydroxides of metal ions under different pH conditions. Then, draw the thermodynamic deposition phase diagram as shown below. Figure 3 As shown.
[0057] Step 3) Based on the thermodynamic deposition phase diagram, NaH₂PO₄ solution was selected as the salt solution to be added to the sealing solution. To generate supercritical carbon dioxide in the sealing solution, an appropriate amount of NaHCO₃ was added to the NaH₂PO₄ solution to obtain the sealing solution. The specific process is as follows:
[0058] Based on the deposition-dissolution equilibrium of MgHPO4, Mg3(PO4)2, and Mg(OH)2, thermodynamic phase diagrams are calculated to determine the deposition order of these three substances, thus identifying the substances that are more easily deposited. For example, the precipitation-dissolution reaction equation for MgHPO4 is established, and the Ksp of the reaction is found in a handbook. Based on the phosphate and monohydrogen phosphate contents at different pH values, the required metal ion contents for MgHPO4, Mg3(PO4)2, and Mg(OH)2 under different pH conditions are calculated. A thermodynamic deposition phase diagram of Mg ions and pH is then plotted. Figure 3As shown in the diagram, the thermodynamic deposition phase diagram indicates a greater tendency for MgHPO4 deposition within the pH range of 4–6. Therefore, adding NaH2PO4 to the sealing solution allows MgHPO4 to be deposited on the substrate surface. The deposition ability of MgHPO4 is enhanced by adding NaHCO3 to raise the solution pH to 6. Therefore, MgHPO4 was determined to be the most suitable pore filler, and pH 6 was the most suitable deposition pH. NaHCO3 was determined to be the buffer added to adjust the pH of the Sc-H2O-Na2HPO4 system, and the initial calculated concentration of Na2HPO4 was 0.1 mol / L.
[0059] In order to generate CO2 by reacting NaHCO3 in NaH2PO4 solution, NaHCO3 is added when the pH of NaH2PO4 solution is adjusted to 4-6. The initial calculated concentration of NaH2PO4 solution is set to 0.1 mol / L.
[0060] Furthermore, according to the thermodynamic deposition phase diagram, in order to improve the deposition ability of MgHPO4, the addition of NaHCO3 was stopped when the pH of the NaH2PO4 solution was increased to 5.5-6.6, thus obtaining a sealing solution formed by NaH2PO4 and NaHCO3.
[0061] In a preferred embodiment of the present invention, when adding NaHCO3 to the NaH2PO4 solution, the addition of NaHCO3 is stopped when the pH of the solution rises to 6, resulting in a sealing solution formed by NaH2PO4 and NaHCO3.
[0062] Step 4) The prepared sealing solution is injected into the reactor, and then the reactor is heated. Under heating conditions, the NaHCO3 in the sealing solution reacts rapidly in the acidic environment of the NaH2PO4 solution to generate carbon dioxide gas. Subsequently, the equipment's chiller is turned on to cool the gaseous carbon dioxide and convert it into supercritical carbon dioxide.
[0063] In this process, after the sealing solution is injected into the reactor, the temperature of the reactor is heated to 40℃~80℃.
[0064] In a preferred embodiment of the present invention, the temperature of the reaction vessel is heated to 60°C after the sealing solution is injected into the reaction vessel.
[0065] Step 5) The prepared bio-magnesium alloy cylinder with a micro-arc oxidation coating is hung on a rack inside the reactor using a wire, and the cylinder is immersed in the sealing solution inside the reactor. The reactor is closed and pressurized. When the reactor reaches the predetermined pressure, timing begins to seal the micro-arc oxidation coating on the surface of the bio-magnesium alloy. After the predetermined sealing time is reached, the reactor is depressurized, and then the reactor is opened to remove the bio-magnesium alloy with the micro-arc oxidation coating sealed. Finally, it is washed with anhydrous ethanol and dried to obtain the bio-magnesium alloy with the micro-arc oxidation coating sealed.
[0066] In this process, the bio-magnesium alloy with a micro-arc oxidation coating on its surface is placed in the sealing solution inside the reactor, and then the reactor is pressurized to a pressure of 8MPa to 15MPa.
[0067] As a preferred embodiment of the present invention, the bio-magnesium alloy with a micro-arc oxidation coating on its surface is placed in the sealing solution in the reactor and then the reactor is pressurized to a pressure of 10 MPa.
[0068] Among them, the bio-magnesium alloy with a micro-arc oxidation coating on its surface is sealed in the sealing solution in the reactor for 10 min to 20 min.
[0069] As a preferred embodiment of the present invention, the bio-magnesium alloy with a micro-arc oxidation coating on its surface is sealed in the sealing solution in the reactor for 15 minutes.
[0070] The preparation of bio-magnesium alloys with a micro-arc oxidation coating on the surface includes the following steps:
[0071] (1) The Mg-Zn-Ca biomagnesium alloy was wire-cut into semi-cylindrical samples with a diameter of 10 mm and a height of 15 mm.
[0072] (2) Drill a 3mm diameter hole on the side of the sample and use a tap to machine the internal thread for subsequent connection of the wire.
[0073] (3) The sample surface was polished in sequence with silicon carbide sandpaper of type 240#, 600#, 1000# and 2000#, and then cleaned and dried to obtain the bio-magnesium alloy sample.
[0074] (4) The cathode of the micro-arc oxidation power supply is connected to a graphite plate, and the anode is connected to the bio-magnesium alloy sample with an aluminum alloy wire.
[0075] (5) Prepare electrolyte: 20.0 g / L Na2SiO3·9H2O, 2.0 g / L NaOH and 3.3 g / L KF·2H2O, pH=13.
[0076] (6) Connect the power supply and perform micro-arc oxidation on the semi-cylindrical sample of bio-magnesium alloy in the electrolyte until a micro-arc oxidation coating is formed on the surface of the bio-magnesium alloy.
[0077] This invention provides a supercritical sealing method for micro-arc oxidation coatings on bio-magnesium alloys based on thermodynamic deposition phase diagrams. The method involves reacting NaHCO3 with an acidic NaH2PO4 solution to generate carbon dioxide, which is then cooled to a supercritical state. Utilizing the superior properties of supercritical CO2, such as its high diffusion capacity (like a gas), low surface tension, and high density (like a liquid), the entropy of the sealing solution system is increased. This allows the sealing solution to fully penetrate the micropores of the micro-arc oxidation coating, sealing the pores through the deposition of metal ions, achieving excellent sealing results and significantly improving the corrosion resistance of the metal. Simultaneously, the method also exhibits good H2 absorption capacity during the sealing process, thus solving the problem of poor sealing results caused by gas difficulty in escaping and hindering pore filling in traditional sealing processes. This further enhances the sealing effect and significantly improves the corrosion resistance of magnesium alloys.
[0078] The following examples and comparative examples illustrate the supercritical sealing method for a bio-magnesium alloy micro-arc oxidation coating based on a thermodynamic deposition phase diagram provided by the present invention.
[0079] Example 1
[0080] 1) Cut the Mg-Zn-Ca biomagnesium alloy into semi-cylindrical samples with a diameter of 10 mm and a height of 15 mm.
[0081] 2) Drill a 3mm diameter hole on the side of the sample and use a tap to machine an internal thread in the hole for subsequent wire connection.
[0082] 3) The sample surface was polished in sequence with silicon carbide sandpaper of grades 240#, 600#, 1000# and 2000#, and then cleaned and dried to obtain the bio-magnesium alloy sample.
[0083] 4) The cathode of the micro-arc oxidation power supply is connected to a graphite plate, and the anode is connected to the bio-magnesium alloy sample with an aluminum alloy wire.
[0084] 5) Prepare the electrolyte: 20.0 g / L Na2SiO3·9H2O, 2.0 g / L NaOH and 3.3 g / L KF·2H2O, pH=13.
[0085] 6) Connect the power supply and perform micro-arc oxidation on the bio-magnesium alloy semi-cylindrical sample in the electrolyte until a micro-arc oxidation coating is formed on the surface of the bio-magnesium alloy, thus obtaining a bio-magnesium alloy cylinder with a micro-arc oxidation coating on the surface.
[0086] 7) Determine the most suitable pore filler by judging the deposition sequence based on the thermodynamic phase diagram.
[0087] Based on the deposition-dissolution equilibrium of MgHPO4, Mg3(PO4)2, and Mg(OH)2, thermodynamic phase diagrams are calculated to determine the deposition order of these three substances, screening out those that are easier to deposit. For example, the precipitation-dissolution reaction equation for MgHPO4 is established, and the Ksp of the reaction is found in a handbook. Based on the phosphate and monohydrogen phosphate contents at different pH values, the required metal ion contents for MgHPO4, Mg3(PO4)2, and Mg(OH)2 at different pH values are calculated, and a deposition phase diagram of Mg ions and pH is plotted. Figure 3 As shown in the phase diagram, it was determined that MgHPO4 has a greater tendency to deposit in the pH range of 4–6. Therefore, adding NaH2PO4 to the sealing solution can obtain MgHPO4 on the substrate surface. By adding NaHCO3 to increase the solution pH to 6, the deposition capacity of MgHPO4 was improved. Therefore, MgHPO4 was determined to be the most suitable pore filler, and the most suitable deposition pH was 6. NaHCO3 was determined to be the buffer added to adjust the pH of the Sc-H2O-Na2HPO4 system, and the initial calculated concentration of Na2HPO4 was 0.1 mol / L.
[0088] 8) Based on the thermodynamic deposition phase diagram, select NaH2PO4 solution as the salt solution to be added to the sealing solution. Add an appropriate amount of NaHCO3 to the NaH2PO4 solution when the pH of the solution is 4 to 6. Stop adding NaHCO3 when the pH of the solution is raised to 6 to obtain the sealing solution.
[0089] 9) Inject the prepared sealing solution into the reactor and heat the reactor to 60°C. Then turn on the equipment's chiller to cool the gaseous carbon dioxide and convert it into supercritical carbon dioxide.
[0090] 10) The prepared bio-magnesium alloy cylinder with a micro-arc oxidation coating is hung on a rack inside the reactor using a wire, and the cylinder is immersed in the sealing solution inside the reactor. The reactor is closed and pressurized. When the pressure reaches 10 MPa, timing begins. After sealing the micro-arc oxidation coating on the surface of the bio-magnesium alloy for 15 minutes, the reactor is depressurized, and then the reactor is opened to remove the bio-magnesium alloy with the micro-arc oxidation coating sealed. Finally, it is washed and dried with anhydrous ethanol to obtain the bio-magnesium alloy with the micro-arc oxidation coating sealed.
[0091] The surface SEM image of the bio-magnesium alloy coating with micro-arc oxidation coating obtained in the embodiments of the present invention is shown below. Figure 4 As shown in (a1), the cross-sectional SEM image of the bio-magnesium alloy with micro-arc oxidation coating sealing obtained in the embodiment of the present invention is shown in (a2).
[0092] from Figure 4As can be seen from the above, the sealing method provided in this embodiment of the invention, under the conditions of a reactor temperature of 60°C (i.e., a supercritical temperature of 60°C), a reactor pressure of 10 MPa, and a sealing time of 15 minutes, produces a dense film thickness of more than 10 nm on the bio-magnesium alloy with micro-arc oxidation coating sealing, with few pores and almost all micropores being well filled.
[0093] The scanning electron probe microanalysis (EMPA) image of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention is shown below. Figure 5 As shown.
[0094] from Figure 5 As can be seen from the diagram, the bio-magnesium alloy with micro-arc oxidation coating sealing obtained in this embodiment of the invention contains Mg, O, and P as the filler at the micropores of the micro-arc oxidation coating. Based on the deposition lines and EPMA results, the filler composition can be determined to be MgHPO4. According to the distribution of P element in the spectrum, MgHPO4 is well filled at the micropores on the surface. While MgHPO4 is also present near the substrate, its filling effect is not as good. This indicates that the sealing solution under supercritical fluid conditions has difficulty penetrating deep into the micropores.
[0095] The XRD pattern of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention is shown below. Figure 6 As shown.
[0096] from Figure 6 As can be seen from the XRD diffraction results of the bio-magnesium alloy with micro-arc oxidation coating sealing obtained in the embodiments of the present invention, not only do the characteristic diffraction peaks of MgSiO3 of the micro-arc oxidation coating appear, but also the expected diffraction peaks of MgHPO4 appear, further verifying the deposition of MgHPO4 in the micro-arc oxidation coating under supercritical conditions. Meanwhile, the diffraction peak intensity increases with increasing temperature, indicating that the content of MgHPO4 on the coating surface increases.
[0097] EIS spectra of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention during long-term immersion. Figure 7 As shown.
[0098] from Figure 7 As can be seen, the micro-arc oxidation coating-sealed bio-magnesium alloy obtained in this embodiment of the invention exhibits arc-inducing resistance for 98 days at 60°C, demonstrating the best corrosion resistance compared to other conditions. Furthermore, its corrosion resistance is significantly improved compared to the unsealed PEO sample. This result further verifies the significant role of micro-arc oxidation coating sealing in a supercritical carbon dioxide environment.
[0099] The macroscopic morphology of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention after immersion in SBF solution is as follows: Figure 8 As shown.
[0100] from Figure 8 It can be seen that, generally, blistering and damage to the coating surface can only be observed 5 days after the appearance of an inductive arc in the electrochemical impedance spectroscopy. However, the micro-arc oxidation coating of the bio-magnesium alloy obtained in this embodiment of the invention only shows black spots on the surface after a 60-day immersion period, but the coating does not suffer large-scale damage.
[0101] Example 2
[0102] The difference between this embodiment and Embodiment 1 is that in this embodiment, when the bio-magnesium alloy with a micro-arc oxidation coating is placed in the reactor, the reactor temperature is 40°C, the reactor pressure is 8 MPa, and the sealing time is 15 min. Other process steps and parameters are the same as in Embodiment 1.
[0103] SEM images of the surface and cross-section of the bio-magnesium alloy with micro-arc oxidation coating obtained in this embodiment of the invention are shown below. Figure 9 As shown. From Figure 9 It can be seen that when the sealing temperature is only 40°C, a relatively large amount of filler is filled into the micropores, and the sealing effect is good, but slightly inferior to the sealing effect of Example 1.
[0104] The EIS spectrum of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention during long-term immersion at 40°C is shown below. Figure 10 As shown. From Figure 10 It can be seen that the Si-PEO sample at -40℃ showed an inductive arc resistance time of 54 days, which is 6 days less than the time shown at 60℃. After sealing treatment under supercritical conditions of 40℃-8MPa, the Rp of the micro-arc oxidation coating increased to 1.5×10⁶ Ω·cm. 2 It has good corrosion resistance, but not as good as at 60℃.
[0105] The macroscopic morphology of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention after immersion in SBF solution at 40°C is as follows. Figure 11 As shown. From Figure 11 It can be seen that some corrosion occurred after 60 days. Overall, its corrosion resistance is good, but its corrosion resistance is not as good as under the condition of 60℃.
[0106] Example 3
[0107] The difference between this embodiment and Embodiment 1 is that in this embodiment, when the bio-magnesium alloy with a micro-arc oxidation coating is placed in the reactor, the reactor temperature is 80°C, the reactor pressure is 8 MPa, and the sealing time is 15 min. Other process steps and parameters are the same as in Embodiment 1.
[0108] SEM images of the surface and cross-section of the bio-magnesium alloy with micro-arc oxidation coating obtained in this embodiment of the invention are shown below. Figure 12 As shown, from Figure 12 It can be seen that when the temperature continues to rise to 80℃, the effect of micropore filling is not significantly improved compared to 60℃.
[0109] The EIS spectra of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention during long-term immersion are as follows: Figure 13 As shown, from Figure 13 It can be seen that the impedance results at 60℃ and 80℃ are very similar within the same period, when Rp decreases to 200kΩ·cm 2 Samples typically exhibit inductive arc resistance rapidly during subsequent immersion. The Si-PEO sample at -80℃ showed inductive arc resistance after 52 days. After sealing under supercritical conditions of 80℃-8MPa, the Rp of the micro-arc oxidation coating increased to 1.6 × 10⁶ Ω·cm. 2 Its corrosion resistance is slightly lower than that at a temperature of 60℃.
[0110] The corrosion morphology of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention after long-term immersion in SBF solution is shown in the figure below. Figure 14 As shown, from Figure 14 It can be seen that compared to the condition of 60℃, there is slight corrosion after 60 days, and the corrosion resistance is good, but the corrosion resistance effect is not as good as the condition of 60℃.
[0111] Example 4
[0112] The difference between this embodiment and Embodiment 1 is that in this embodiment, when the bio-magnesium alloy with a micro-arc oxidation coating is placed in the reactor, the reactor temperature is 60°C, the reactor pressure is 12 MPa, and the sealing time is 15 min. Other process steps and parameters are the same as in Embodiment 1.
[0113] The surface and cross-sectional SEM images of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention are shown below. Figure 15 As shown, from Figure 15 It can be seen that when the pressure increases to 12 MPa, although a large number of precipitate particles can be observed on the coating surface, the filler inside the coating is slightly reduced.
[0114] The XRD analysis diagram of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention is shown below. Figure 16 As shown, from Figure 16 As can be seen from the XRD diffraction pattern, the material after sealing the pores has not changed, and its composition remains MgSiO3 and MgHPO4. At pressures of 12 MPa and 15 MPa, the number and intensity of the MgHPO4 diffraction peaks did not change significantly; however, at a pressure of 10 MPa, the intensity of the MgHPO4 diffraction peaks increased, indicating a higher content of MgHPO4 produced on the surface.
[0115] The EIS spectra of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention during long-term immersion are as follows: Figure 17 As shown, from Figure 17 It can be seen that the sample exhibited inductive arc after immersion for 38 days. Compared to Si-PEO-10MPa, which only showed inductive arc in EIS results after immersion in SBF solution for 98 days, the impedance value of the Si-PEO-12MPa sample was consistently lower than that of the Si-PEO-10MPa sample during the immersion period, and there was no obvious Rp abrupt change. This indicates that the surface filler has a good protective effect on the substrate, but not as good as the Si-PEO-10MPa sample, i.e., the sample of Example 1.
[0116] Macroscopic morphology of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention after immersion in SBF solution is shown in the figure. Figure 18 As shown, from Figure 18 As can be seen, compared to 10 MPa, the coating showed corrosion after 100 days. Under this condition, the corrosion resistance was good, but not as good as that of Example 1 at 10 MPa.
[0117] Example 5
[0118] The difference between this embodiment and Embodiment 1 is that in this embodiment, when the bio-magnesium alloy with a micro-arc oxidation coating is placed in the reactor, the reactor temperature is 60°C, the reactor pressure is 15 MPa, and the sealing time is 15 min. Other process steps and parameters are the same as in Embodiment 1.
[0119] The surface and cross-sectional SEM images of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention are shown in Figure 19. Figure 19 As can be seen, when the pressure increases to 15 MPa, the thickness of Si-PEO also decreases, and MgHPO4 cannot be observed at the cross-section. Its sealing effect is good, but slightly inferior to the sealing effect of Example 1.
[0120] The EIS spectra of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention during long-term immersion are as follows: Figure 20 As shown, from Figure 20 It can be seen that when the pressure is increased to 15MPa, the Si-PEO-15MPa sample showed inductive arc after immersion for 13 days, which is shorter than the time (17 days) for the unsealed coating to show inductive arc. The Si-PEO-15MPa sample is completely opposite to the Si-PEO-10MPa sample, showing a decreasing trend in impedance, so the coating is in a state of gradual dissolution.
[0121] The macroscopic morphology of the micro-arc oxidation coating sealing bio-magnesium alloy obtained in this embodiment of the invention after immersion in SBF solution is as follows: Figure 21 As shown, from Figure 21 It can be seen that corrosion appeared on a certain area of the coating after 20 days. Although its corrosion resistance is not as good as that at 10 MPa, i.e. not as good as that of Example 1 at 10 MPa, the corrosion resistance of the present invention is good overall.
[0122] A comparison of Examples 1-5 of this invention shows that the supercritical sealing method for micro-arc oxidation coating of bio-magnesium alloy based on thermodynamic deposition phase diagram provided by this invention, by selecting a solution formed by adding NaH2PO4 solution to NaHCO3 as the sealing solution, controlling the temperature at 40℃~80℃ after the sealing solution is injected into the reactor, controlling the sealing solution pressure at 8MPa~15MPa during sealing, and controlling the sealing time at 10min~20min, can achieve good sealing effect and significantly improve the corrosion resistance of the metal. However, the best sealing effect can be achieved at a temperature of 60℃, a sealing pressure of 10MPa, and a sealing time of 15min, which can maximize the improvement of the corrosion resistance of the metal.
[0123] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A supercritical sealing method for bio-magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram, characterized in that: The steps include: Using phosphate as the sealing solution component, the phosphate ionization equilibrium at different pH values was established, and the phosphate distribution pattern of the phosphate system with pH changes was obtained. The deposition-dissolution equilibrium of metal ion phosphides and hydroxides of phosphate conversion membranes in supercritical carbon dioxide environment at different pH values was established, and the thermodynamic deposition phase diagram was obtained. According to the thermodynamic deposition phase diagram, NaH2PO4 solution was selected and NaHCO3 was added to obtain the sealing solution; The sealing solution is injected into the reactor to be heated, and then the cooling machine is turned on to convert the generated carbon dioxide gas into supercritical carbon dioxide; The bio-magnesium alloy after micro-arc oxidation is placed in a sealing solution in a reactor and pressurized to seal the micro-arc oxidation coating on the surface of the bio-magnesium alloy.
2. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to claim 1 is characterized in that: When the pH of the NaH2PO4 solution is controlled at 4-6, NaHCO3 is added to increase the pH of the solution to 5.5-6.6 to obtain a sealing solution.
3. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to claim 2 is characterized in that: NaHCO3 is added to the NaH2PO4 solution to increase the pH of the sealing solution to 6.
4. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to claim 1 is characterized in that: The sealing solution is injected into the reaction kettle and heated to a temperature of 40°C to 80°C.
5. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to claim 4 is characterized in that: The sealing solution was injected into the reaction kettle and heated to 60°C.
6. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to claim 1 is characterized in that: The pressure of the micro-arc oxidized bio-magnesium alloy after pressurization in the sealing solution in the reactor is 8MPa-15Mpa.
7. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to claim 6 is characterized in that: The pressure of the micro-arc oxidized bio-magnesium alloy after pressurization in the sealing solution in the reactor is 10 MPa.
8. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to claim 1 is characterized in that: The micro-arc oxidation coating on the surface of the biological magnesium alloy is sealed in the sealing solution in the reaction kettle for 10 minutes to 20 minutes.
9. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to claim 8 is characterized in that: The micro-arc oxidation coating on the surface of the biological magnesium alloy is sealed in the sealing solution in the reactor for 15 minutes.
10. The supercritical sealing method of biological magnesium alloy micro-arc oxidation coating based on thermodynamic deposition phase diagram according to any one of claims 1 to 9, characterized in that: The micro-arc oxidation of the bio-magnesium alloy comprises the following steps: The Mg-Zn-Ca bio-magnesium alloy wire was cut into semi-cylindrical samples with a diameter of 10 mm and a height of 15 mm; A hole with a diameter of 3 mm was punched on the side of the sample, and an internal thread for subsequent connection of the wire was machined in the hole with a tap; The sample surface was polished with silicon carbide sandpaper of model 240#, 600#, 1000#, and 2000# in sequence, and then cleaned and dried to obtain the biological magnesium alloy sample; The cathode of the micro-arc oxidation power supply is connected to the graphite plate, and the anode is connected to the biological magnesium alloy sample with an aluminum alloy wire; Prepare electrolyte: 20.0g / L Na2SiO3·9H2O, 2.0g / L NaOH and 3.3g / L KF·2H2O, pH=13; The magnesium alloy micro-arc oxidation coating was prepared in pulse mode with the following electrical parameters: voltage of 380±10V, current density of 3A / dm 2 , the duty cycle is 30%, and the processing time is 30±2min; The power supply is turned on, and the bio-magnesium alloy semi-cylindrical sample in the electrolyte is subjected to micro-arc oxidation until a micro-arc oxidation coating is formed on the surface of the bio-magnesium alloy.
Citation Information
Cited By
Preparation method of wear-resistant and corrosion-resistant modified composite coating on surface of hardware product
CN122105403A
A method for preparing a modified composite coating for wear and corrosion resistance on a hardware surface
CN122105403B